Sm/Ti co-substituted bismuth ferrite multiferroics: Reciprocity between tetragonality and piezoelectricity - Jha P.K.; Jha P.A.; Singh P.; Ranjan R.; Dwivedi R.K. (My University, 2025)
BiFeO3 (BFO) systems co-modified with Ti, Sm and Sm-Ti have been investigated for piezoelectricity together with dielectric and multiferroic properties. Structural studies revealed the coexistence of orthorhombic and rhombohedral (R3c) phases for x > 0.12. Impurity phases were shown to have hardly any effect on the remanent magnetization, which rather depends on the Fe-O-Fe bond angle. The dielectric loss was reduced considerably by substitution. A correlation between the piezoelectric coefficient and tetragonality was observed in these samples. BFO co-substituted with Sm-Ti exhibited a high piezoelectric coefficient with better ferroic properties, which revealed a unique combination of green piezoelectricity and multiferroicity. © the Owner Societies 2017.